Prospective Teachers’ Ability to Self Reflect Their Teaching Simulation in Micro Teaching Class in ELE Undiksha - P.R.Y. Antari; L.P. Artini; N.L.P.E.S. Dewi (Jurnal IKA, 2021)
This study aimed to: 1) describe how the students learn to reflect their teaching simulation in microteaching class.2) describe what the students think about the benefit of learning to reflect teaching simulations in microteaching class. This study was conducted in ELE Undiksha Singaraja,especially sixth grade students because by doing self-reflection, students who will be an English teacher can improve their teaching. It is very important the sixth semester of ELE students in Undiksha Singaraja to be aware of strengths and weaknesses of own teaching for knowing the parts of teaching that need to be maintained and improved. This study was descriptive qualitative. This study used self-reflective journal as  an instrument which was descriptively analyzed. The result showed 1) The students reflect their teaching based on exploring their weaknesses after doing teaching simulation in the classroom such as lack in classroom management and technical problem during teaching 2) Students got the benefit of learning based on the input from the audience, after watching the recorded simulation and based on their self-observation start from how they prepare until the end of the simulation.Keywords: Self-Reflection, Reflective Teaching, Self-Reflective Journal